2020
DOI: 10.5534/wjmh.190038
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoplasmic Reticulum Stress Response in Male Reproductive Physiology and Pathology: A Review

Abstract: Endoplasmic reticulum (ER) stress, defined as prolonged disturbances in protein folding and accumulation of unfolded proteins in the ER. Perturbation of the ER, such as distribution of oxidative stress, iron imbalance, Ca 2+ leakage, protein overload, and hypoxia, can cause ER stress. The cell reacts to ER stress by activating protective pathways, called the unfolded protein response (UPR), which is comprised of cellular mechanisms aimed for maintaining cellular homeostasis or, in case of excessively severe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 84 publications
2
44
0
Order By: Relevance
“…We performed Western blot analysis to check ER stress protein markers for inositol requiring enzyme 1 (IRE1)-C-jun-N-terminal kinase (JNK) pathway in testicular tissues. Excessive ER stress can induce cellular apoptosis through three signaling pathways (ATF6, IRE1, and PERK) [23]. The IRE1-JNK pathway was analyzed to determine VC-induced testicular germ cell apoptosis (Figure 4A,C,D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed Western blot analysis to check ER stress protein markers for inositol requiring enzyme 1 (IRE1)-C-jun-N-terminal kinase (JNK) pathway in testicular tissues. Excessive ER stress can induce cellular apoptosis through three signaling pathways (ATF6, IRE1, and PERK) [23]. The IRE1-JNK pathway was analyzed to determine VC-induced testicular germ cell apoptosis (Figure 4A,C,D).…”
Section: Resultsmentioning
confidence: 99%
“…ER stress activation could be key signaling mechanism for germ cell apoptosis [23,42]. A previous study has reported that the ER chaperone Grp 78 is predominately present in pachytene spermatocytes, suggesting that the ER stress signaling pathway has a vital role in the process of spermatogenesis [43].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to prove the activation of ER-stress mediated apoptosis due to NOX-induced OS following tIRI. The involvement of ER stress-induced apoptosis of both male and female reproductive cells and different diseases has been reported and reviewed in several studies ( Liu et al, 2016 , Karna et al, 2019 ). It was also reported that cadmium-induced GCA resulted from mitochondrial cytochrome-c release, upregulation of GRP67 and CHOP and phosphorylation of eIF2α and JNK in testes ( Ji et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes scavenge free radicals and prevent oxidative damage by enhancing cellular defenses [37]. ROS can cause extensive damage to DNA, proteins, and lipids in germ cells [38,39]. Our results show that MOTILIPERM decreases the levels of ROS/RNS and MDA and increases levels of the antioxidant enzymes SOD, GPx, catalase, and GPx 4.…”
Section: Discussionmentioning
confidence: 63%